Shaping The Character Of The Students Through Example Of Teachers - Yuli Choirul Umah (EDUCATIO : Journal of Education, 2016)
The government made an effort to solve the problem by proclaiming moral decadence "Character Education" in every level of education. Character education is a holistic educational process that connects the moral dimension to the social realm in the students life as the foundation to establish quality generations who are Able to Live Independently and have the truth principle that can be accounted for. Character is a "behavior" not a 'knowledge'. So, in the practice of character education requires not only the theory or the concept its self, but Also the direct models of the teacher. Therefore, it can be internalized by the students well Because it is not only taught but Also exemplified. The implementation of character education in schools is more accurate through modeling approaches, modeling (uswah) conducted by the teacher. Teacher's exemplary is needs to be created Because a teacher is a central figure in the school that the students' attention always for them. Teachers should really be an example not only the conveyor of science information, but Also includes transfer's activity of virtuous noble character personality in order to form student's character as a national asset that will be the determinant of the existence of this nation